Treatment of Venous Thromboembolism in Elite Athletes: A Suggested Approach to Individualized Anticoagulation - Nazha, Bassel; Pandya, Bhavi; Spyropoulos, Alex C.; Kessler, Craig M. (Seminars in Thrombosis and Hemostasis, 2018)
Venous thromboembolism (VTE) is a leading cause of morbidity with potentially detrimental career consequences in elite athletes. Their unique predisposing factors entail a higher-than-expected VTE incidence. Anticoagulation treatment is challenging, especially among those athletes wishing to resume their competitive activities. The authors review the current VTE treatment guidelines from the perspective of treating elite athletes. They then provide an expert opinion individualized treatment approach based on the pharmacokinetic properties of direct oral anticoagulants that permits tailoring the drug's timing to the athlete's competitive endeavors. They also present low-molecular-weight heparin as an alternative. The proposed risk management approach allows mitigation against VTE recurrence, reducing the chance of major bleeding, and honoring the athlete's self-determination to resume their career while accepting the risks involved. A shared decision making with the athlete and his/her team along with the presence of adequate resources are key components. Ultimately, the authors hope this work will serve as a stepping stone to validated VTE treatment regimens that consider the particularities of elite athletes.
Keywords: direct oral anticoagulants; athletes; venous thromboembolism; expert opinion; anticoagulation; deep vein thrombosis; pulmonary embolism